2018
DOI: 10.1051/e3sconf/20185101007
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the wind power potential in the Romanian coastal environment - moving from onshore to offshore

Abstract: In the past few years in Romania the total installed capacity reached 3025MW. Because the Europe Union is pursuing to obtain an increase in renewable energy by 2020 to cover 20% of the energy consumption with renewable energy maybe in the near future in Romania the wind energy parks will start to be build off shore where the wind energy is more powerful. From this perspective, the present work is trying to provide a better picture to the wind energy resources at the Romanian shore. The measured data was provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Regarding the Black Sea wind conditions, the previous research indicated that the western part of this basin present in general more important wind resources [8,9]. As for the Romanian coastal environment, it is estimated that the sites located on the northern areas may present interest for the development of a wind project [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Black Sea wind conditions, the previous research indicated that the western part of this basin present in general more important wind resources [8,9]. As for the Romanian coastal environment, it is estimated that the sites located on the northern areas may present interest for the development of a wind project [10,11].…”
Section: Introductionmentioning
confidence: 99%